The Congress of Vienna : power and politics after Napoleon - Vick, Brian E., 1970- (Harvard University Press, 2014)
[Description]Historians have dismissed the pageantry of the Vienna Congress as window dressing when compared with the serious maneuverings of sovereigns and statesmen. By seeing these two dimensions as interconnected, Brian Vick reveals how one of the most important diplomatic summits in history managed to redraw the map of Europe and the international system.